2018
DOI: 10.3390/vaccines6030058
|View full text |Cite
|
Sign up to set email alerts
|

The Future of Influenza Vaccines: A Historical and Clinical Perspective

Abstract: For centuries, the development of vaccines to prevent infectious disease was an empirical process. From smallpox variolation in Song dynasty China, through the polysaccharide capsule vaccines developed in the 1970s, vaccines were made either from the pathogen itself, treated in some way to render it attenuated or non-infectious, or from a closely related non-pathogenic strain. In recent decades, new scientific knowledge and technologies have enabled rational vaccine design in a way that was unimaginable before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 99 publications
(100 reference statements)
0
21
0
5
Order By: Relevance
“…Population-based studies of seasonal influenza have typically shown this type of mortality distribution according to age ( Fig. 1C ) [ 12 ]. Several cohort studies have shown that the hospitalization rate of influenza was highest for the age group of 0 – 4 years compared to that in other age groups, which indicates that children under the age of 5 years could be more vulnerable to influenza and/or more severely affected [ 13 14 ].…”
Section: Covid-19-associated Morbidity and Mortality According To Agementioning
confidence: 99%
“…Population-based studies of seasonal influenza have typically shown this type of mortality distribution according to age ( Fig. 1C ) [ 12 ]. Several cohort studies have shown that the hospitalization rate of influenza was highest for the age group of 0 – 4 years compared to that in other age groups, which indicates that children under the age of 5 years could be more vulnerable to influenza and/or more severely affected [ 13 14 ].…”
Section: Covid-19-associated Morbidity and Mortality According To Agementioning
confidence: 99%
“…Secondly, they do not produce a cross-reactive immune response that can neutralize diverse influenza virus strains. Cross-reactivity is necessary because of the antigenic plasticity of the viral membrane protein hemagglutinin (HA), which leads to antigenically drifted viruses and potential mismatches with the vaccine strains [ 3 ]. This shortcoming can be addressed by developing new vaccines targeting the more antigenically conserved regions of the influenza virus [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since isolation of the first influenza virus in the mid 1930's [1], control of the virus has been a longpursued global public health goal. From the early inactivated vaccines to the current recombinant quadrivalent vaccines, there is no doubt that science and technology have stepped up to this challenge [2][3][4]. However, the constant genetic shifts and drifts of the virus remain the most relevant factors hindering efforts at disease control; the current annual incidence of influenza-like illness (ILI) in Latin America ranges between 4.7 and 15.4% [5].…”
Section: Introductionmentioning
confidence: 99%